The role played by prison officers in ensuring ART adherence on prison inmates who are HIV/AIDS infected (KweKwe Central and Conemara Prisons) - Tlou, Keeteretsi (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.